Morphological and molecular data on Phyllodistomum (Digenea: Gorgoderidae) from Brazil, with the description of a new species parasitizing Hoplias malabaricus (Bloch, 1794) (Osteichthyes, Erythrinidae) - Dias, K. G.A. [UNESP]; Pérez-Ponce De León, G.; Da Silva, R. J. [UNESP]; Vieira, D. H.M.D. [UNESP]; Leite, L. A.R. [UNESP]; De Azevedo, R. K.; Abdallah, V. D. (Cambridge University Press (CUP), 2023)
Phyllodistomum pepirense n. sp. is described from the urinary bladder of Hoplias malabaricus (Bloch, 1794), sampled in the Jacaré-Pepira River in São Paulo state, Brazil. The isolates of the new species were recovered as a monophyletic group in the phylogenetic analysis of the 28S rRNA gene, which showed the new species as the sister taxa of Phyllodistomum virmantasi Pinacho-Pinacho, Sereno-Uribe, Hernández-Orts, García-Varela & Pérez-Ponce de León, 2021, a species sampled from an eleotrid fish in Southeastern Mexico. The new species differs morphologically from P. virmantasi by having a larger body size, slightly lobed testes and ovary, a mostly intercaecal uterus, slightly diverticulated caeca, and vitelline masses irregularly shaped. The new species is also readily distinguished from other species of Phyllodistomum Braun, 1899 reported from freshwater fishes in Brazil - namely, P. rhamdiae Amato & Amato, 1993 and P. spatula Odhner, 1902. The new species is herein described based on morphological characteristics, molecular data from D1-D3 domains of the 28S rRNA gene, host association, and geographical distribution.
Keywords: 28S; Digenea; Erythrinidae; Hoplias; South America; taxonomy